The press and literature representation in the Trilogy of Happiness, by Camilo Castelo Branco - Greco, Leticia De Freitas [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2021)
Driven by the Industrial Revolution and the liberal revolutions of the 18th and 19th centuries, the Press grows and develops as the number of readers increases. Novels, on the other hand, lose their status of art to also become a commodity. In Portugal, Camilo Castelo Branco is the first writer to live off his works, so he moves between different textual genres, representing this new marketing reality. The objective of this work is to analyze the three works that constitute the so-called Trilogy of Happiness: Onde esta a Felicidade? (1856), Um Homem de Brios (1856) and Memorias de Guilherme do Amaral (1863), to verify how the relation between production and consumption of newspapers and novels are portrayed by the author, who introduces a selfreflective literature in the trilogy.
Keywords: Camilo Castelo Branco; Literature; Press; Trilogy of Happiness